Unveiling the glymphatic system’s role in brain aging: A comprehensive biomarker and modifiable intervention target - Yuanyuan Fang; Wenxi Luo; Hao Huang; Lusen Ran; Yuqin He; Chang Cheng; Yao Yao; Yuxiang Hou; Haibo Zheng; Dengji Pan; Shabei Xu; Xiang Luo; et al. (Proceedings of the National Academy of Sciences, 2026)
The focus of this study is to investigate the role of diffusion tensor imaging along the perivascular space (DTI-ALPS) index in brain aging. To address this, we first examined the association of DTI-ALPS with aging hallmarks among 40,488 UK Biobank (UKB) participants. Next, we developed normative brain age models incorporating the DTI-ALPS index from 12,401 healthy UKB adults and validated in UKB-ADNI and UKB-TALENT datasets. Finally, we explored the relationship between brain age gap (BAG) with peripheral organ function, chronic diseases, proteomics, and genetics, while identifying modifiable factors in a longitudinal cohort. The findings revealed that DTI-ALPS index correlated with chronological age, telomere length, brain structure, and cognition. A brain age model integrating the DTI-ALPS index achieved good accuracy in the UKB ( r = 0.756) and replicated well in two independent datasets (UKB-ADNI: r = 0.766; UKB-TALENT: r = 0.724), with choroid plexus volume emerging as an additional contributor. Musculoskeletal health was a key driver for brain aging in females, while pulmonary metrics prevailed in males. Neurodegenerative and metabolic disorders increased BAGs, imparting increased mortality risk. Protein-wide and genome-wide analysis identified 154 BAG-related proteins and 11 loci. Modifiable factors, particularly systolic blood pressure below 120 mmHg, were strongly associated with reduced BAGs. Overall, the DTI-ALPS index is a promising brain aging biomarker, offering insights into links between brain and peripheral health, and highlighting sex-stratified therapeutic strategies. Aggressive blood pressure control may mitigate brain aging and promote long-term brain health.